Impact of Buzhong Yiqi Prescription on the Gut Microbiota of Patients with Obesity Manifesting Polycystic Ovarian Syndrome. (15th March 2021) - Ni, Zhexin; Cheng, Wen; Ding, Jie; Yao, Ruipin; Zhang, Danying; Zhai, Dongxia; Zhou, Ling; Yu, Chaoqin
Abstract : Gut microbiota disorders are closely related to polycystic ovarian syndrome (PCOS). Buzhong Yiqi prescription (BZYQ) has a significant clinical effect on the treatment of patients with obesity exhibiting PCOS and phlegm-dampness syndrome caused by spleen deficiency (SPSD). Hence, this study aimed to explore gut microbiota and fecal metabolite alterations in such patients treated with BZYQ. Fifty eligible patients with obesity manifesting PCOS and SPSD participated and agreed to undergo 3 months of BZYQ treatment. Results showed that BZYQ significantly alleviated the serum dehydroepiandrosterone sulfate p < 0.001 and testosterone levels p < 0.001 and markedly changed the gut microbiota structure in these patients. Furthermore, 106 differential fecal metabolites and 14 KEGG enrichment pathways were quantified. The phylum Spirochaetae and the genera [Eubacterium]_rectale_group, Escherichia-Shigella, and Fusicatenibacter were significantly more abundant, but Megamonas was significantly less abundant after treatment than before treatment. Disorders in the gut microbiota and fecal metabolites of these patients were closely related to hyperandrogenemia and insulin resistance. In conclusion, BZYQ could ameliorate the serum androgen level and had an impact on the gut microbiota and metabolites in patients with obesity manifesting PCOS and SPSD.